Efektifitas Metode Pembelajaran Kitab Kuning di Madrasah Diniyah Pondok Pesantren Al-Mahalli Brajan Wonokromo Pleret Bantul Tahun Ajaran 2013/2014 - Azuma Fela Sufa (Universitas Alma Ata, 2014)
Azuma Fela Sufa, Effective Learning Method Yellow Book in Madrasah Diniyah Pondok Pesantren Al-Mahalli Brajan Wonokromo Pleret Bantul academic year 2013/2014. Islamic Religious Education Program School of Religion Yogyakarta Alma Ata, 2014. The background of this research, the methods used are generally not fully assist students in understanding the yellow book. Therefore, the boarding school chaplain tried to explore their creativity to find other methods that can support learning in the yellow book pesantren Al-Mahalli. So that the students will be easier to learn to use the yellow book and they were delighted to learn of the yellow book. Thus, researchers want to know what the method used by the cleric for their teaching and learning processes, effective or not after using these methods as well as factors inhibiting and supporting factors in learning the yellow book. This research includes qualitative naturalistic. The subjects of the study are caregivers, chaplain/cleric and the students Wustho class boarding school al-Mahalli. Methods of data collection using observation, interviews and documentation. Data analysis techniques used in the field before and during field model of Miles and Huberman. The results obtained from this study is that the methods used in the yellow book learning is effective and runs well. Judging from the results of their observations are very enthusiastic about learning the yellow book and will affect their understanding. Then apart from observations and interviews, the researchers took the data as a value and when viewed from the average value is good, then the method used was effective and well. Such inhibiting factors in learning, problem of time, the majority of students are not familiar yellow book, the method sorogan, often seen some students do not focus, in mengkhatamkan book takes a long time. Supporting factors, the chaplain/ cleric experienced in accordance with their respective fields, the availability of facilities and infrastructure are adequate, the majority of students live in boarding school so that automatically terkondusif by the environment. Efforts made by the boarding school chaplain include, in addition to the afternoon of madrasah diniyah done at night so that learning can be optiimal yellow book. As well as the cleric always tried to explore their creativity in order etode-learning methods used in the yellow book can be run properly and effectively.